High-pressure phase equilibrium data for aromatic components of wine: Carbon dioxide/n-butanal system - Marta Vázquez da Silva (2000)
Phase equilibrium data, measured in a static-type apparatus, for the system carbon dioxide/n-butanal at 303.2 and 313.2 K and for pressures up;to the critical point are presented. The results are correlated by the Soave-Redlich-Kwong and Peng-Robinson equations of state, and the associated interaction parameters are given.